Effect of moderate-intensity exercise training on GDNF signaling pathway in testicles of rats after experimental diabetes type 1 induction. (September 2020) - Samadian, Zahra; Tofighi, Asghar; Razi, Mazdak; Ghaderi Pakdel, Firouz; Tolouei Azar, Javad
Abstract: Aims: The spermatogenesis failure is reported as the main complication for diabetes and the moderate-intensity exercise (EX) is shown to ameliorate the diabetes-induced impairments both at spermatogenesis and sperm levels. Thus, the current study was done to investigate the possible effect of EX in the sole and simultaneous form with insulin on the network between Sertoli and spermatogonial stem cells (SSCs) by focusing on niche factor Glial cell-derived neurotrophic factor (GDNF). Methods: For this purpose, 30 mature male Wistar rats were divided into control and experimental type 1 diabetes (T1D)-induced groups. Then the T1D-induced animals were subdivided to sedentary T1D-induced (ST1D), EX + T1D, insulin (INS) + T1D and EX + INS + T1D groups. The general histological changes of testicles, mRNA and protein contents of GDNF and its special receptors gfrα1 and c-RET were evaluated and compared between groups. Results: EX in the sole and simultaneous form with INS significantly (p < 0.05) diminished the T1D-induced histological damages, amplified the GDNF expression, and enhanced the gfrα1 and c-RET mRNA and protein contents compared to ST1D group. Conclusion: In conclusion, the EX in the sole form promotes spermatogenesis by up-regulating the GDNF signaling system. Moreover, EX remarkably amplifies the insulin-induced ameliorative effect on spermatogenesis.